TAPPING LABOUR SHORTAGE AND THE STALEMATE IN FEMALE LABOUR PARTICIPATION: A DISAGGREGATE LEVEL ANALYSIS OF RUBBER SMALLHOLDER SECTOR IN KERALA - T. Siju, K. Tharian George and Binni Chandy (Rubber Science, 2015)
One of the major constraints faced by the rubber smallholder sector in Kerala is the growing shortage of rubber tappers. Increasing female labour participation is considered as one of the better options to address this issue. The present analysis reveals that the share of female labour in the total workforce of rubber tappers in the state was 7.5 per cent with notable regional variations. The study shows that the continuance of the lower female labour participation in the smallholder sector is more than a supply side issue with important socio-economic and region-specific aspects. Analysis of age and caste compositions of rubber tappers, tapping tasks and wage rates did not reveal any significant entry barrier for female rubber tappers across the regions. However, the unique socio-economic milieu encompassing tapping job in the smallholder sector, especially the smaller size of holdings, appears to be the critical barrier in ensuring adequate supply of female labour. Hence, any long-term policy has to consider the multi-dimensional aspects of the issue for promoting group approaches rather than implementing ad hoc measures for addressing the shortage of rubber tappers.